Cumhuriyet konulu anma serisi posta pulları katalogu (1933-1993) ve grafik cözümlemeleri - Düzenli, Şükran; Kavuran, Tamer (My University, 2005)
The stamps demonstrate to the economic, sociological and culturel progres a country. In this respect structure and contents of the anniversary stamps have gained importance. Anniversary stamps are published for the remambrance of on event, a person or for the sake of propaganda. The subject of study in to examine the anniversary series of the post stamps that werw publish for commemoration of foundation of republic (1933-1993). It was aim to describe the connected collection of library, hatch to selfs and indexs of the list of scientific publications. For the direction of results it was include graphic analysis of these stamps. There stamps were the graphic product, if it was thinking of the contents, it was appear with this study the designs must be more corefully and for this direction suggestions submitted.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: İletişim; Pul; Grafik; Tasarım